Floor Failure Characteristics in Deep Island Longwall Panel: Theoretical Analysis and Field Verification - Pengpeng Wang; Yixin Zhao; Qingshan Ren; Yaodong Jiang; Cun Zhang; Yirui Gao (Geofluids)
Floor failure in deep coal mining above confined aquifers with high-water pressure may induce floor water inrush disasters. Considering the effects of mining stress and nonuniformly distributed water pressure, a mechanical calculation model of the island longwall panel in up-dip mining was established, and the stress distribution and floor failure characteristics were analyzed. The failure characteristics of the floor at NO. 2129 panel in Xingdong coal mine were detected by the borehole televiewer and microseismic monitoring system to validate the theoretical model. The results indicated that the floor failure characteristics along the strike and inclination of the island longwall panel in up-dip mining were “asymmetric inverted saddle-shaped” and “spoon-shaped,” respectively. The maximum floor failure depths before and after roof hydraulic fracturing (RHF) were 45.7 m and 29.1 m, respectively. The theoretical calculation results of the maximum depths of floor failure were 45.1 m and 29.9 m, respectively. The theoretical failure characteristics were consistent with those measured on site. The stress concentration magnitude and floor failure depth on the side of the isolated coal pillar were greater than those of other areas, and the water-inrush-prone zones were concentrated on the side of the isolated coal pillar near the intersection of the working face and the roadway. The research results could provide a certain reference for floor failure and water inrush mechanisms under complex geological conditions in deep mining.